Immigration, crime and justice - McDonald, William F. (William Frank), 1943- (JAI Press, 2009)
This volume examines the nexus between immigration and crime from all of the angles. It addresses not just the evidence regarding the criminality of immigrants but also the research on the victimization of immigrants; on human trafficking; domestic violence; the police handling of human trafficking; the exportation to crime problems via deportation; the vigilantes at the U.S. border; the role of the non-immigration police in the control of immigration; and, the criminalization of immigration policy.
Keywords: Noncitizen criminals.; Criminal justice, Administration of.; Criminology.; Emigration and immigration.; Immigrants -- Crimes against.; Criminels étrangers.; Criminologie.; Émigration et immigration.; criminology.; migrations (events); immigration.; Migration period (Medieval culture or period); emigration.; Crime & criminology.; Migration, immigration & emigration.; Social Science -- Emigration & Immigration.; Law -- Emigration & Immigration.; Noncitizen criminals; Criminal justice, Administration of; Criminology; Emigration and immigration; Immigrants -- Crimes against; Noncitizens.